2016
DOI: 10.18819/ijavs.2016.1548
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Students Attitude towards Agricultural Science Subject in Secondary Schools in Olamaboro Local Government Area of Kogi State, Nigeria

Abstract: ABSTRACT:The study assessed factors that influence students '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This means that that one of the factors that can influence the respondents in pursuing agriculture is the advice and support of their families. Students are often reluctant to pursue or even explore diverse degree possibilities without the parental or families approval or support (Adejoh et al, 2016). This result is corroborated by the works of Esters & Bowen (2004) and Fizer (2013) who reported that the family influences individuals in deciding what degree they will undertake in college.…”
Section: Chi Square Testmentioning
confidence: 95%
“…This means that that one of the factors that can influence the respondents in pursuing agriculture is the advice and support of their families. Students are often reluctant to pursue or even explore diverse degree possibilities without the parental or families approval or support (Adejoh et al, 2016). This result is corroborated by the works of Esters & Bowen (2004) and Fizer (2013) who reported that the family influences individuals in deciding what degree they will undertake in college.…”
Section: Chi Square Testmentioning
confidence: 95%
“…Getnet and Asrat (2012) indicated that the poor image of persons involved in agriculture needs to be changed and the young people are the ideal catalysts for such change given their greater propensity and willingness to adopt new ideas, concepts and technology which are all critical to changing the way agriculture is practiced and perceived. Perceptions of students on career prospects in agriculture were poor societal value of farmers (Adejoh et al, 2016).…”
Section: Professional Statusmentioning
confidence: 99%
“…Agrawal and Agrawal (2017) and Sood (2014) reported that the interest of farmers was important in farming and their occupational satisfaction affected their incentive to invest in farming whereas report of National Centre of Universities and Business (2015), Akubari (2016), Adejoh et al (2016) and Jayne (2010) found that the young people were usually not interested in this field of work, in large part due to their perception of farming being antiquated and unprofitable and youth regard farming as a 'dirty activity' due to lack of proper facilities and agriculture was regarded as an employer of the last resort to younger generation. Similarly Leavy and Smith (2010) and Narain et al (2015) also found farming as unattractive sector for youth.…”
Section: Personal Interest and Satisfactionmentioning
confidence: 99%
“…Parents' background, education inclusive (Adejoh et al, 2016) play significant role in determining the agricultural career of children and their finding showed that parents also influence students' attitude towards agricultural science subject in secondary schools. This study was an effort to address the deficiency in curricular objective of agricultural science in the area of skills development and preparation for occupations in agriculture among secondary school students.…”
Section: Parents' Education In Learning Agricultural Sciencementioning
confidence: 99%
“…In other words, the category of Nigerian citizenry of young people, to which the majority of secondary school students belong, is a promising cohort that can easily align with the arguments of tapping into the highly resourced agricultural sector of the country if the right attitude and interest is promoted among them. Unfortunately, Adejoh et al (2016) reported decline in the number of students who choose agricultural science among their list of subjects in senior secondary schools in Nigeria. Similarly, Baliyan & Nenty (2015) recorded the picture of a poor and declining enrollment trend in agriculture in senior secondary schools in Botswana as a major concern for agricultural educators across the country.…”
Section: Introductionmentioning
confidence: 99%